Multi-responsive supramolecular hydrogels for drug delivery. Issue 83 (2nd September 2015) - Shi, Yang; Wang, Zhongyan; Zhang, Xiaoli; Xu, Tengyan; Ji, Shenglu; Ding, Dan; Yang, Zhimou; Wang, Ling
Abstract : We reported a versatile method to prepare responsive supramolecular hydrogels. Abstract : We reported in this study a versatile method to prepare multi-responsive supramolecular hydrogels for drug delivery application.